Pembentukan Karakter Melalui Pembelajaran Problem Based Learning - Taufikin, Taufikin (THUFULA, 2017)
This paper examines how Build the characters towrd the complex problems. Each educational institution needs to provide an alternative solution to to solve the problems. One of the alternatives in bulding the character is by applying the strategy of problem based learning. It is expected that learners will have noble character such as religious, responsibility, hard work, independent, democratic, tolerant, concerned about environment and social religion, love of homeland and nationalisme.